СКОРОЧЕННЯ З ЦИФРОВИМИ СИМВОЛАМИ У КОМУНІКАЦІЯХ ЗА ДОПОМОГОЮ ТЕХНІКИ (Науковий журнал «Наукові записки Національного університету «Острозька академія»: серія «Філологія», 2012)
The article deals with the features of shortenings with the help of digits in the English language technology-mediated discourse. Digits functions and specific shortening methods were described. Linguistic status of lexemes shortened with the help of digits was also studied.